Empowering Green Trademark For Ecolabel Certification In Malaysia - Ahmad Ridzuan, Mohamad Nazmi (2019)
The use of ecolabels in the market is increasing day by day. It is used to inform the consumer about green products and services that are available in the market. The increasing demand and the benefit given by ecolabels has made it essential for companies to certify their products or services. However, the validity of a product or service that is awarded with current ecolabels is still doubtful, such as the requirement needed by a product or service to be certified and how it can ensure the trustworthiness of the ecolabel. Besides that, the certification mark under trademark law is also used to certify products or services that have satisfied certain criteria of certification. Both ecolabel and certification have similar functions, but each of them consists of different criteria, processes and evaluation. It would be more beneficial for ecolabels to interface with green trademark as it allows protection in terms of intellectual property rights. Plus, it will strengthen the legal mechanism and guidelines for future ecolabels in Malaysia, especially as the current standards are still inadequate to monitor all the certifications in the market. The objectives of this study are to study the criteria to obtain the Energy Efficiency Label (EEL) for four specific electrical appliances as advocated by the Energy Commission of Malaysia, to analyze the certification process of EEL for four specific electrical appliances advocated by the Energy Commission of Malaysia, to examine the evaluation for the certification process of EEL for four specific electrical appliances advocated by the Energy Commission of Malaysia, and to suggest effective practices for the EEL certification of four specific electrical appliances which interface with the theoretical baselines of green trademarks in terms of criteria, certification processes and evaluation. This research is an exploratory case study using the qualitative method. Semi-structured interviews with thirteen experts on intellectual property and ecolabels in Malaysia were conducted. The data collected was analyzed using thematic analysis. From the data collected, the integration of ecolabels and green trademarks can be done in terms of criteria, process and evaluation. This study also has proposed effective practices for the certification of EEL that interface with the theoretical baselines of green trademark that can be used for future certification. As a conclusion, the interface of ecolabel certification and green trademark in terms of criteria, process and evaluation should be done for future certifications as a way to improve the certification standards in Malaysia which can benefit certification bodies, industries, consumers and the environment.